International servitization of SMEs in emerging markets: antecedents and boundary conditions - Zahoor, Nadia; Christofi, Michael; Nwoba, Arinze Christian (My University, 2023)
Purpose: Product-service innovation (i.e. servitization) is providing opportunities to small and medium-sized enterprises (SMEs) to offer services that are directly coupled to their products. Despite scholarly efforts on servitization in domestic markets, the determinants of international product-service innovation remain unclear. Therefore, this study draws insights from dynamic capability (DC) view and aims to examine the international human capital and international product-service innovation relationship. Specifically, the authors argue that the effect of international human capital on international product-service innovation is mediated by international inter-organizational marketing capability (IIMC) and moderated by international market complexity. Design/methodology/approach: The authors test the conceptual model using structural equation modeling on a sample of 211 SMEs operating in United Arab Emirates (UAE) – an emerging market economy. Findings: The results show that IIMC mediates the relationship between international human capital and international product-service innovation. The authors further found that the indirect relationship between international human capital and international product-service innovation is strengthened when international market complexity increases in magnitude. Originality/value: This study advances the knowledge on international servitization by examining international human capital and IIMC as the determinants and international market complexity as a moderator. Data collection in the UAE contributes to empirical research on international servitization from emerging markets.
Keywords: Dynamic capability; Emerging markets; Inter-organizational marketing capabilities; International human capital; International market complexity; International servitization